THE IMPORTANCE OF EXCHANGE PROGRAMS IN EDUCATION - Azatova Nargiza, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides a comprehensive analysis of the importance of exchange programs in education within the framework of educational innovation and integration. It examines academic, cultural, linguistic, and professional dimensions of exchange programs  and  highlights  their  role  in  improving  educational  quality,  academic mobility, and international cooperation.